Novel cellulose/NbOPO 4.nH 2O hybrid material from sugarcane bagasse - Voorwald, Herman Jacobus Cornelis [UNESP]; Pereira, Paulo Henrique Fernandes [UNESP]; Cioffi, Maria Odila Hilario [UNESP]; da Da Silva, Maria Lucia Caetano Pinto (North Carolina State Univ Dept Wood & Paper Sci, 2011)
In recent years studies concerning the applications of lignocellulosic/ inorganic couples have resulted in the development of an interesting class of functional materials. In this work a cellulose/NbOPO 4.nH 2O hybrid using cellulose from surgacane bagasse was prepared and characterized in order to test for adsorption applications. The preparation process was conducted by carrying out metallic niobium dilution in hydrofluoric acid in the presence of nitric acid, then adding boric acid to form the complex and, finally, the cellulose sugar cane bagasse was added. Concentrated phosphoric acid was also inserted to precipitate hydrous niobium phosphate particles in the cellulose fiber. This material was characterized by X-ray diffractometry (XRD), thermogravimetry (TG/DTG), and scanning electronic microscopy (SEM) connected to an energy dispersive spectrophotometer (EDS). Results by SEM/EDS show that NbOPO 4.nH 2O was present in structure of the cellulose. During the preparation of the material, using boric acid it was observed that the formation of precipitate occurred in a shorter time than the material prepared without boric acid.
Keywords: Cellulose; Hybrid organic/inorganic; Hydrous niobium phosphate; Sugarcane bagasse; Boric acids; Cellulose fiber; Energy dispersive; Niobium phosphates; Organic/inorganic; Preparation process; Scanning electronic microscopy; SEM/EDS; Adsorption; Boride coatings; Functional materials; Hybrid materials; Hydrofluoric acid; Niobium; Niobium compounds; Nitric acid; Phosphoric acid; Sugar cane; Sugars; Thermogravimetric analysis; X ray diffraction analysis; Bagasse; Coatings; Gravimetry; Hydrofluoric Acid; Nitric Acid; Phosphoric Acid; Sugar Cane; Thermal Analysis; X Ray Diffraction; Saccharum